Численность птиц в различных ландшафтах Северного Приазовья - Филонов, К.П. (Вестник зоологии, 1972)
The peculiarities of bird population were studied in different landscapes of the North Azov Sea аrеа. Data аrе given оn quantity of the species in each landscape, their number and zoomass, dominating species аrе distinguished. Emberiza hortulana L., Corvus frugilegus L., Sylvia communis L a t h. dominate in forest landscape. In ореn landscapes — Melanocorypha calandra L., Calandrella cinerea G m., Alauda arvensis L. and Corvus frugilegus L. аrе most numerous species. Species-synantrops dominate in populated areas. Sterna sandvicensis L a t h., Sterna hirundo L. and S. albifrons Р а l l. dominate at the coast and in islands of the Molochny liman.